SPIRITUALITAS KOMUNAL NUSANTARA: MODEL KONSELING PASTORAL BERBASIS GOTONG ROYONG - Tuerah, Joshua; Gagola, Patricia; Salenda, Richi; Lintjewas, Francien (PT. Giat Konseling Nusantara, 2025)
In the era of globalization, rapid social change has impacted the lives of Indonesians. Societal values ​​have shifted from communal values ​​to a more individualistic lifestyle as a result of modernization and advances in information technology. As a result, many people feel a loss of meaning in life, alienated from their communities, and experience increasingly complex mental and spiritual stress. Lestari and Gunawan emphasize the importance of a contextual pastoral approach: